Regeneration and conservation : Świebodzki station area - Bolhuis, Klaas Jan; Brajović, Tamara; Gendek, Izabela; Makhatay, Volha; Marchwicka, Barbara; Mohacsi, Katalin (AESOP, 2010)
The Świebodzki Station, out of action since 1991, built in 1842 in classical style as a connection hub, is an attractive landmark. Located 800 metres from Rynek, 1,5 km from Wrocław Główny station and 9 km from the airport, the station houses a dance club. A market stretching over the tracks is mostly informal, self organising, well-known and well-visited. Hotly debated, the station and its surroundings have been subjected to numerous studies and strategies. Despite current uses, the area does not live up to its full potential of central location, vacant land, potential rail-airport interchange and valuable historic building. Wrocław’s development opportunities as EURO2012 host city and 2016 European Cultural Capital offers the possibility of developing this site into a unique integrated mixed use area which we conceive as the Golden Gateway to the city. The design of the ‘golden gateway to the city’ consists of three elements: a gateway, an icon, and a place, inspired respectively by Sheffield’s Gold Route, Wrocław’s Renoma department store and the CAT (City Airport Train) connection between Vienna and its airport. The place is already a multi-modal node and appropriate as a gateway for a quick and high quality rail connection between the airport to the city centre, reusing existing tracks to accommodate the 2.2 million passengers expected from 2014.
Book of proceedings: Urban change : The prospect of transformation